ANTICORRUPTION CULTURE AS THE BASIS FOR THE FORMATION OF EFFECTIVE MECHANISMS FOR THE PREVENTION OF CORRUPTION - PARKHOMENKO-KUTSEVIL , Oksana (Theory and Practice of Public Administration, 2019)
The purpose of the work is to carry out a systematic analysis of the formation and implementation of anticorruption policy in Ukraine. The methodology of the research is based on systematic analysis, comparative analysis, the use of methods of deduction and induction, generalization, which made it possible to systematize scientific approaches to the concept of “anticorruption culture”, to identify the constituent concepts, to propose ways to improve anti-corruption policy. The scientific novelty consists in conceptualizing the notion of anticorruption culture, it is proposed to develop and implement the Concept of formation of anticorruption culture in Ukraine. Conclusions Anticorruption culture is a world-view of citizens formed by means of pedagogical methods and techniques aimed at intolerance and non-acceptance of corruption, continuous improvement of its knowledge in the system of anti-corruption legislation, continuous improvement of its knowledge, dissemination of its knowledge among the youth and population of the country. The development and implementation of the Concept for the formation of anticorruption culture in Ukraine is proposed. Defined sections of this legal document. The formation of the anticorruption culture of society consists of: forming a clear understanding of the essence of corruption in a society, reporting on the level of mass consciousness its true price, that is, the entire spectrum and the danger of its socially destructive consequences; Clarification of the importance and available mechanisms of public participation in the prevention and combating of corruption; detailed public coverage of the state’s anti-corruption activities, ensuring the openness and transparency of state bodies on relevant issues; dissemination among citizens information on the basic standards of activity of state institutions; the general anti-corruption education of the population, conducting information and training events of specific content for target audiences in the areas characterized by the worst corruption situation, and especially the anti-corruption education of civil servants; the spiritual rehabilitation of the nation, which will lead to a significant reduction of the selfish-consumer component in the worldview of citizens, by returning to the values of the Orthodox civilization, part of which Ukrainian society has been for centuries, in conjunction with patriotic upbringing; development, consolidation in the public consciousness and gradual practical realization of a clear vision of Ukraine’s future as a country whose development is not compatible with shameful social phenomena such as corruption.